Adsorption Studies of I-Naphthaleneacetic Acid and 2,4-Dichlorophenoxyacetic Acid on Activated Carbon in Aqueous Solution and Oil Palm Tissue Culture Media - Sarmijan, Norhafizah (2002)
A study on the adsorption of activated carbon on oil palm culture media was carried out in two main parts, the adsorption of plant growth regulators I-naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) and root initiation of oil palm tissue culture. Four commercially available activated carbons, namely ACl, AC2, AC3 and AC4 were used in this study. The adsorption of NAA and 2,4-D by activated carbons were determined using UV Nis spectrophotometer. The adsorption of NAA and 2,4-D at different concentrations increased rapidly at the initial stage and then followed by a slower uptake until the equilibrium is established in 40 and 30 minutes. respectively. The maximum uptake was achieved at higher concentration for both of the plant growth regulators. The higher maximum uptake was obtained for higher surface area of the activated carbons. The adsorption isotherms have been obtained at various concentrations. The adsorption isotherm for NAA on AC3 was better fitted to Langmuir equation compared to other activated carbons. On the other hand, Freundlich equation was slightly better fitted to the adsorption of NAA for other activated carbon samples. It was found that the adsorption capacity of NAA on AC3 was higher compared to the other activated carbons. Adsorption isotherm of 2,4-D showed that the Langmuir equation isotherm was better fitted to the experimental data for AC 1 and AC3, but AC2 and AC4 are better fitted to the Freundlich equation. It was observed that AC4 showed the highest adsorption capacity. The n value of AC4 indicated that AC4 was the effective adsorbent for 2,4-D. The ability for root initiation of shoots from the oil palm explants was studied on different treatments. The results indicate that there is no significant difference between the clones but the different samples of activated carbon added into the rooting medium showed a highly significant difference. Addition of activated carbon in the rooting medium improved the overall rooting capacity.